Analysis of flow-induced instability in a redesigned steam control valve. (25th May 2015) - Bolin, Chris; Engeda, Abraham
Abstract: Industrial steam turbines represent one of the largest fractions of prime movers. Regardless of the steam-turbine application being considered, speed and/or load control will be required. Speed control is the primary control loop for all turbine applications, industrial as well as utility. The inlet of industrial steam turbine is usually controlled by a single valve, or a series of valves (multi-valve assembly) working in concert. These valves are required to operate under wide ranges of valve openings and pressure ratios. As a turbine governing valve, the venturi valve, has been widely used in steam turbines to regulate inlet flow in the last 40 years. But as turbine output power become larger, a number of valve failure incidences started to be reported and improving the valve designs became a high priority. Despite numerous investigations to eliminate valve failure, the attempts were not fully successful due to the complicated nature of the fluid–structure interaction mechanisms, and the basic mechanism causing valve vibration and failure is still far from being fully understood. As a continuation of previous valve studies, a newly designed valve has been investigated experimentally and. This paper presents detailed experimental investigations to clarify the mechanisms of valve instability caused by unsteady flows around the valve. A result of the asymmetric unstable flow, noise and vibration characteristics of the valve together with an overall performance assessment of the valve is presented. Highlights: A steam turbine valve was tested to reduce flow non-axisymmetry and instability. Instabilities were not removed completely but some progress was made. It was difficult to visualize the mechanism that triggered instability. This newly-designed valve tested was more stable than previous valves studied.